Pengaruh Financial Literacy, Lifestyle, dan Locus of Lontrol terhadap Financial Behavior Penggunaan Paylater: (Studi Kasus Mahasiswa di Kota Bandung) - Kinaya, Cyntia Octavia; Kosadi, Ferry (Jurnal Ilmu Sosial, Manajemen, Akuntansi dan Bisnis, 2024)
This study aims to describe financial behavior, financial literacy, lifestyle, and locus of control and analyze the influence of financial literacy, lifestyle, and locus of control on the financial behavior of students using Paylater in Bandung. Using a quantitative method with a descriptive and verification approach, a sample of 100 respondents was taken through accidental sampling, with data collected via questionnaires. The analysis was conducted using multiple linear regression. Descriptive results show that the financial behavior, financial literacy, lifestyle, and locus of control of pay later users in Bandung are categorized as high. Partially, financial literacy and locus of control have a significant positive influence on financial behavior, while style has a positive but not significant influence. Simultaneously, these three variables influence financial behavior positively and significantly, with a correlation of 0.742 and a contribution of 55%.